Calidad de vida en el adulto mayor institucionalizados en hogares geriátricos una revisión narrativa (2021)
The present study aims to describe the context of the older adult population with respect to the quality of life in geriatric or institutionalized homes and to determine their living conditions, in this sense, to identify the factors that affect, improve and / or impact this population.